\(dy/dx= -10^(3x^2-4) ln10(6x)\)

\(dy/dx=(-6x ln10)10^(3x^2-4)\)

\(dy/dx=(-6x ln10)10^(3x^2-4)\)

Question

asked 2021-06-06

Find derivatives of the functions defined as follows: \(\displaystyle{y}={x}^{{{e}{x}}}\)

asked 2021-05-25

Use the rules for derivatives to find the derivative of each function defined as follows. \(\displaystyle{y}={2}{\tan{{5}}}{x}\)

asked 2021-03-06

Find derivatives of the functions defined as follows. \(y=3 \cdot 4^{x^{2}+2}\)

asked 2021-03-07

Find derivatives of the functions defined as follows. \(y=(te^{t}=2)/(e^{2t}+1)\)

asked 2021-05-11

Use the rules for derivatives to find the derivative of function defined as follows.

\(\displaystyle{q}={\left({e}^{{{2}{p}+{1}}}-{2}\right)}^{{{4}}}\)

\(\displaystyle{q}={\left({e}^{{{2}{p}+{1}}}-{2}\right)}^{{{4}}}\)

asked 2021-03-12

Find the derivatives of the following functions.

\(\displaystyle{f{{\left({x}\right)}}}={{\cos{{h}}}^{{{2}}}{\left({3}{x}-{1}\right)}}\)

\(\displaystyle{f{{\left({x}\right)}}}={{\cos{{h}}}^{{{2}}}{\left({3}{x}-{1}\right)}}\)

asked 2021-04-30

Derivatives of the sum of functions Find the derivative of the following functions.

\(\displaystyle{f{{\left({x}\right)}}}={3}{x}^{{{4}}}+{7}{x}\)

\(\displaystyle{f{{\left({x}\right)}}}={3}{x}^{{{4}}}+{7}{x}\)

asked 2021-05-03

Find the first partial derivatives of the following functions.

\(\displaystyle{f{{\left({x},{y}\right)}}}={4}{x}^{{{3}}}{y}^{{{2}}}+{3}{x}^{{{2}}}{y}^{{{3}}}+{10}\)

\(\displaystyle{f{{\left({x},{y}\right)}}}={4}{x}^{{{3}}}{y}^{{{2}}}+{3}{x}^{{{2}}}{y}^{{{3}}}+{10}\)

asked 2021-04-19

consider the product of 3 functions \(\displaystyle{w}={f}\times{g}\times{h}\). Find an expression for the derivative of the product in terms of the three given functions and their derivatives. (Remeber that the product of three numbers can be thought of as the product of two of them with the third

\(\displaystyle{w}'=\)?

\(\displaystyle{w}'=\)?

asked 2021-02-14

Calculate the derivatives of the functions. Then find the values of the derivatives as specified.

\(\displaystyle{f{{\left({x}\right)}}}={4}-{x}^{{{2}}};{f}'{\left(-{3}\right)},{f}'{\left({0}\right)},{f}'{\left({1}\right)}\)

\(\displaystyle{f{{\left({x}\right)}}}={4}-{x}^{{{2}}};{f}'{\left(-{3}\right)},{f}'{\left({0}\right)},{f}'{\left({1}\right)}\)